Political values of society: analyze political ideology of Western Europe and Kazakhstan (Journal of Philosophy Culture and Political Science, 2018)
The article deals with political values, the ideological direction of the political parties of Western Europe and Kazakhstan. It was comparative analysis of the problems of formation of ideologies and their influence on the formation of political parties and party systems in Western Europe and Kazakhstan. In Western democracies parties act as independent subjects in the political process. In Kazakhstan’s political system, the party does not occupy such an important place. The main social function of the party today is the function of maintaining and strengthening bilateral relations between the authorities and society.Key words: political parties, party systems, political values and ideology.